PELATIHAN PEMASARAN PUDING MELALUI MEDIA SOSIAL BAGI IBU-IBU WARGA ASRAMA BRIMOB AMPELDENTO KABUPATEN MALANG - Ellyn Eka Wahyu; Pudji Herijanto; Masreviastuti Masreviastuti; Halid Hasan; Ahmad Suyono (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Since 2018, social media had grown very rapidly. But in facts, this potential had not been maximized because according to APJII data, only 1.9 percent of people use social media to increase their income through selling online. In the Asrama Brimob Detasemen B, Ampeldento, Kabupaten Malang, there are many wives of soldiers who was housewives that did not have  any skills and also had income  steadyness. In addition, the second problem was that there are many wives of soldiers that only know about using social media as an activity to expand their friends. They also did not understand how to use social media as a tools of promoting and selling products, so it was hoped that it could be a source of additional income for the soldier's wife. From this problems, the Community Service Team (PkM) provided an alternative by giving a training to sold  various Pudding Product Marketing Training by using Instagram social media so that the markets will be wider. All participants were able to practice from the training results, by selling  products such as cakes and puddings through Instagram social media to the general public. We  also hoped that they could increased the income in the future.